2013
DOI: 10.1111/nph.12581
|View full text |Cite
|
Sign up to set email alerts
|

Caterpillar attack triggers accumulation of the toxic maize protein RIP2

Abstract: SummarySome plant-derived anti-herbivore defensive proteins are induced by insect feeding, resist digestion in the caterpillar gut and are eliminated in the frass. We have identified several maize proteins in fall armyworm (Spodoptera frugiperda) frass that potentially play a role in herbivore defense. Furthermore, the toxicity of one of these proteins, ribosome-inactivating protein 2 (RIP2), was assessed and factors regulating its accumulation were determined.To understand factors regulating RIP2 protein accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 73 publications
4
60
0
Order By: Relevance
“…We used 18 biological replicates for each treatment, each of which was fed to 18 naïve FAW caterpillars for 3 d. Caterpillar mass was measured at the beginning and the end of the bioassay and used to calculate relative growth rates as described earlier (Hoffmann and Poorter, 2002;Mohan et al, 2008). Caterpillar feeding on plants is associated with the deposition of insect oral secretions and saliva, which can trigger herbivore-induced defenses in plants (Louis et al, 2013;Chuang et al, 2014a;Acevedo et al, 2015). To understand the effect of maize chitinases Pr4 and Endochitinase A on such plant defenses triggered by caterpillar herbivory, we fed fifth instar FAW larvae in inverted clip cages for 3 h as described in our previous study .…”
Section: Faw Bioassaysmentioning
confidence: 99%
“…We used 18 biological replicates for each treatment, each of which was fed to 18 naïve FAW caterpillars for 3 d. Caterpillar mass was measured at the beginning and the end of the bioassay and used to calculate relative growth rates as described earlier (Hoffmann and Poorter, 2002;Mohan et al, 2008). Caterpillar feeding on plants is associated with the deposition of insect oral secretions and saliva, which can trigger herbivore-induced defenses in plants (Louis et al, 2013;Chuang et al, 2014a;Acevedo et al, 2015). To understand the effect of maize chitinases Pr4 and Endochitinase A on such plant defenses triggered by caterpillar herbivory, we fed fifth instar FAW larvae in inverted clip cages for 3 h as described in our previous study .…”
Section: Faw Bioassaysmentioning
confidence: 99%
“…In maize, it is known that caterpillar feeding increases JA levels both locally and systemically, which results in the activation of a suite of herbivore defenserelated genes including genes encoding enzymes in the JA biosynthetic pathway (Erb et al, 2009a;Shivaji et al, 2010). Furthermore, downstream genes that encode direct defense proteins such as proteinase inhibitor, chitinase, and Ribosome-Inactivating Protein2 are induced by caterpillar feeding (Shivaji et al, 2010;Chuang et al, 2014). Previous studies have shown that Mir1-CP accumulation in maize upon caterpillar feeding is dependent on both JA and ET pathways (Harfouche et al, 2006;Ankala et al, 2009).…”
mentioning
confidence: 99%
“…Since the proRIP2 is not specifically expressed in seed tissue as is the case with proRIP1, the question remains whether activation in vivo is caused by exposure to endogenous proteases (as shown for proRIP1 during germination) or by exposure to proteases introduced by invading pests or pathogens [67]. Chuang et al [69] reported that proRIP2 can be processed in the midgut of fall armyworm into the active form.…”
Section: Biological Activity Of Cereal Rip Domainsmentioning
confidence: 99%